DEBATING PRACTICE TO SUPPORT CRITICAL THINKING SKILLS: DEBATERS’ PERCEPTION - Kinanthi Tiasadi (Universitas Lampung, 2020)
English debate is an attractive activity for students where they can practice English and communication skills, also could strengthen critical thinking through the activities. However, the activity is rarely implemented in Indonesian curriculum even though they’ve started implementing High Order Thinking Skill (HOTS) in their learning material. To fill this void, this study aims at exploring the debater’s perception who had experience debate activity for years. Debate activity is mostly found in co-curriculum activity where it is not obligatory for students. In order to understand the component of HOTS, the researcher used the construct by Facione (1990) to characterize Critical Thinking (CT) skills that can be learned. The purpose of this study is to dig the debater’s experiences during their time of joining debate Community and how they perceive CT skills trough the activity. The study presented in a qualitative method. Two university students that have different experiences in debating who also from different university and debate community were chosen as the participant. The data were acquired with in-depth interview from each of the participants. The data were analyzed using thematic analysis by Braun Clarke (2006) where the researcher state themes from the data that is important and related to the question. The finding showed that both of them felt debate activity is contributing to sharpen their CT skills such as analysis, self-regulation, and evaluation. An interesting finding also found that one of the participants experience CT disposition as an extension of CT skills. http://dx.doi.org/10.23960/aksara/v21i1.pp1-16